Neurological manifestations of lysosomal disorders and emerging therapies targeting the CNS. (January 2018) - Giugliani, Roberto; Vairo, Filippo; Kubaski, Francyne; Poswar, Fabiano; Riegel, Mariluce; Baldo, Guilherme; Saute, Jonas Alex
Summary: Lysosomal disorders have been an area of interest since intravenous enzyme replacement therapy was successfully introduced for the treatment of Gaucher's disease in the early 1990s. This treatment approach has also been developed for several other lysosomal disorders, including Fabry's disease, Pompe's disease, lysosomal acid lipase deficiency, and five types of mucopolysaccharidosis. Despite the benefits of enzyme replacement therapy, it has limitations—most importantly, its ineffectiveness in treating the neurological components of lysosomal disorders, as only a small proportion of recombinant enzymes can cross the blood–brain barrier. Development of strategies to improve drug delivery to the CNS is now the primary focus in lysosomal disorder research. This Review discusses the neurological manifestations and emerging therapies for the CNS component of these diseases. The therapies in development (which are now in phase 1 or phase 2 clinical trials) might be for specific lysosomal disorders (enzyme replacement therapy via intrathecal or intracerebroventricular routes or with fusion proteins, or gene therapy) or applicable to more than one lysosomal disorder (haemopoietic stem cell transplantation, pharmacological chaperones, substrate reduction therapy, or stop codon readthrough). The combination of early diagnosis with effective therapies should change the outlook for patients with lysosomal disorders with neurological involvement in the next 5–10 years.